-4.5(7x-6.5)=-23.5

Simple and best practice solution for -4.5(7x-6.5)=-23.5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4.5(7x-6.5)=-23.5 equation:


Simplifying
-4.5(7x + -6.5) = -23.5

Reorder the terms:
-4.5(-6.5 + 7x) = -23.5
(-6.5 * -4.5 + 7x * -4.5) = -23.5
(29.25 + -31.5x) = -23.5

Solving
29.25 + -31.5x = -23.5

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-29.25' to each side of the equation.
29.25 + -29.25 + -31.5x = -23.5 + -29.25

Combine like terms: 29.25 + -29.25 = 0.00
0.00 + -31.5x = -23.5 + -29.25
-31.5x = -23.5 + -29.25

Combine like terms: -23.5 + -29.25 = -52.75
-31.5x = -52.75

Divide each side by '-31.5'.
x = 1.674603175

Simplifying
x = 1.674603175

See similar equations:

| 52-4x=10-10x | | 3x-2(x-3)+4(x+1)=-5 | | 2x-102-10x=42 | | -9(5-5.5k)=26.5 | | 14-8m= | | -77-10x=165+x | | 5ab*3= | | 5r-14=-44 | | 10x-1=6x+10 | | =9xy^2+6xy-5x | | 24+8y-16w= | | 2(7x-13)=16 | | 5x+(x+2)-3(x-4)=35 | | 5x+3+3x=83 | | 2(7x+13)=16 | | 2x-5+12=7(x-2) | | 3x-7=5+6x | | -2d-9.5d=-2.15 | | 8x+28=60 | | -3(-3r-6)=63 | | 8.5x=6y-c | | 6x-12=20x | | x-4(x+1)-2(x+3)=-60 | | 2(3x-6)=20x | | 8.5c+2.5-8c=22.5 | | x^6-44x^3-4x^2+580=0 | | -88-6x-4x=62 | | 30ab+36ac= | | 2y+3=3y-38 | | 42+14x=14x+21 | | 5+.30p=p | | 15t+4=4g |

Equations solver categories